The partisan politics of foreign policy: explainingTurkey’s ‘nationalist turn’ and its involvement in the 2020 Karabakh war - Babayev, Azar; Jumayeva, Lala (Routledge, Taylor & Francis Group, 2025)
This article addresses the party politics of foreign policy through a theoretically informed analysis of the political survival imperative in a domestic context. Building on recent research on party ideologies and political survival/power-seeking, it offers a fresh perspective on the influence of partisan politics on foreign policy. Drawing on qualitative data, including expert interviews, the article uses the case of Turkey as a hybrid, and thus unstable, regime to examine the partisan aspects of foreign policy with a focus on two basic links between party politics and foreign policy behaviour: party ideologies and party leadership. Specifically, the article argues that the ruling AKP’s need for domestic survival led to increasingly nationalist, populist behaviour and the formation of an alliance with the main nationalist party MHP, which in turn led to the dominance of a nationalist discourse in Turkish foreign policy, contributing to coercive or risky international moves. This is best exemplified by the AKP government’s strong support for Azerbaijan in the 2020 Karabakh war.
Keywords: Political parties -- Influence -- Foreign policy -- Turkey.; Populism -- Turkey.; Nationalism -- Political aspects -- Turkey.; Ideology -- Political aspects.; Political leadership -- Turkey.; International relations -- Political aspects.